Pengaruh Model Pembelajaran Team Game Tournament (TGT) Berbantuan Media Interaktif Mentimeter terhadap Hasil Belajar IPAS - Syifa Siti Nurhasanah; Rana Gustian Nugraha; Dety Amelia Karlina (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research was carried out when students saw a lack of enthusiasm when studying material on a Hindu-Buddhist kingdom, which was triggered by the fact that the material was very dense and there was a lot of memorization. The Team Game Tournament (TGT) learning model assisted by the use of Mentimeter interactive media is considered to be an appropriate alternative solution to improve the science and science learning outcomes of class IV students on Hindu-Buddhist kingdom material. The aim of this research is to determine the influence on students' science learning outcomes after implementing the Team Game Tournament (TGT) learning model and Mentimeter interactive media, as well as finding out the difference in influence between using the TGT model and using conventional learning models on fourth grade students' scienceas learning outcomes. on royal material with a Hindu Buddhist style. This research uses an experimental method with a quasi-experimental design. The research population was all students in class IV elementary school at SDN Tegalkaong with the research sample being students in class IV A and IV C at SDN Tegalkalong. The instrument used was a written test on royal material with a Hindu Buddhist pattern.